Crude extract and fractions from Eugenia uniflora Linn leaves showed anti-inflammatory, antioxidant, and antibacterial activities - Tamires Rocha Falcão; Aurigena Antunes de Araújo; Luiz Alberto Lira Soares; Rhayanne Thaís de Moraes Ramos; Isabelle Cristinne Ferraz Bezerra; Magda Rhayanny Assunção Ferreira; Manoel André de Souza Neto; Maria Celeste Nunes Melo; Raimundo Fernandes de Araújo; Andreza Conceição Véras de Aguiar Guerra; Juliana Silva de Medeiros; Gerlane Coelho Bernardo Guerra (BMC, 2018)
Abstract Background This study showed phytochemical composition and evaluates the anti-inflammatory, and analgesic activities of crude extract (CE) and fractions from E. uniflora Linn leaves. Methods Polyphenols present in crude extract (CE), in aqueous fraction (AqF), and ethyl acetate (EAF) treated fractions from E. uniflora Linn leaves were shown by chromatographic analysis in order to conduct a phytochemical characterization. Antibacterial activity was evaluated based on minimum inhibitory concentrations (MICs) determined using the agar dilution method. Doses of 50, 100, and 200 mg/kg of the CE and fractions were applied for conducting in vivo models (male Swiss mice, 8-10 weeks old). The peritonitis experimental model was induced by carrageenan following of Myeloperoxidase activity (MPO), Total glutathione and malondialdehyde (MDA), IL-1β and TNF-α levels by spectroscopic UV/VIS analysis. Antinociceptive activity was evaluated based on an abdominal writhing model and hot plate test. The results were statistically evaluated using one-way analysis of variance (ANOVA), followed by Bonferroni's post-hoc test. The level of statistical significance was p < 0.05. Results High-performance liquid chromatography with photodiode array detection (HPLC-DAD) detected varying concentrations of gallic acid, ellagic acid, and myricitrin in the CE and fractions obtained from E. uniflora Linn leaves (0.05-0.87%w/w, 0.20-0.32%w/w, and 1.71-6.56%w/w, respectively). In general, the CE had lower MIC values than the fractions, including the lowest MIC against the MRSA strain. The CE and AqF also significantly reduced leukocyte migration and MPO activity (p < 0.05). In addition, AqF significantly reduced IL-1β and TNF-α levels (p < 0.05). Furthermore, the CE and fractions exhibited an antioxidant effect (p < 0.05) and peripheral analgesic activity (p < 0.05). Conclusions The CE and fractions from the studied E. uniflora Linn leaves exhibited antibacterial, anti-inflammatory, antioxidant, and analgesic activity in the performed assays.